Influence of core hardness on bending strength of tooth in cylindrical gears under quasistatic loading conditions - Bozca, M. (WILEY-BLACKWELL, 2008)
Dynamically loaded mechanical components can withstand overloading if they are designed by considering sufficient safety of margin for the static strength. In this study, the influence of core hardness on bending static strength of the tooth in cylindrical hardened gears is investigated experimentally. For this purpose, shot peened and unpeened gears having different core hardness and comparable surface hardness are tested on a pulsator test rig, which provides a quasi-static loading condition by means of a servomotor. All test gears are made of 20MnCr5 steel and have the same geometry (module m = 5 mm). Average static load for fracture is measured. The relationship between the applied load and bending stress is known. Hardness profiles from the surface to the core of the test gears were measured. Strength is assumed to be a function of depth depending hardness to justify fracture initiation on the surface under bending static load conditions. Tooth root failures originating from the surface were observed experimentally. It is found that the shot peening treatment and core hardness have no considerable influence on the bending strength of the tooth under static loading conditions.
Keywords: bending strength of tooth; core hardness; gears; FATIGUE; TEETH; Engineering; Materials Science